1997
DOI: 10.1093/bja/79.4.530
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia for the surgery of emphysema

Abstract: Thoracic anaesthesia is now established in a third age. The first age related to surgery for infective conditions, predominantly tuberculosis, the second was defined by surgery for bronchogenic cancer and the third is surgery for respiratory failure. The anaesthetic imperatives of this latest age are epitomized by emphysema, with some variants treated with lung transplantation and, recently, surgery for the oxymoron, lung volume reduction. Small areas of emphysematous changes are common in the general populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…However, our patient characteristics and lung function data were identical to those described by Tschernko et al (3). It would therefore seem reasonable that PEEP i levels were also high in the present study, particularly as our patients were studied during positive pressure ventilation, which further aggravates dynamic hyperinflation and PEEPi in patients with severe emphysema (20). In patients with normal lung function, and in volunteers, positive pressure-respiration with PEEP depletes the intrathoracic vascular bed and the heart, decreasing both pulmonary, right ventricular (RV) and LV end-diastolic dimensions (21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 76%
“…However, our patient characteristics and lung function data were identical to those described by Tschernko et al (3). It would therefore seem reasonable that PEEP i levels were also high in the present study, particularly as our patients were studied during positive pressure ventilation, which further aggravates dynamic hyperinflation and PEEPi in patients with severe emphysema (20). In patients with normal lung function, and in volunteers, positive pressure-respiration with PEEP depletes the intrathoracic vascular bed and the heart, decreasing both pulmonary, right ventricular (RV) and LV end-diastolic dimensions (21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 76%
“…Prolonged one lung ventilation for bilateral surgery can cause rupture of a giant bulla on contralateral lung. It can lead to potential life-threatening situations such as pneumothorax, pneumopericardium, hypoxemia, and death in spite of cardiopulmonary bypass (7).…”
Section: Discussionmentioning
confidence: 99%
“…Episodic hypoxaemia and hypotension, temporarily corrected by this apnoea manoeuvre, are markers of dynamic hyperinflation affecting venous return and pulmonary blood flow [4, 5]. Despite direct visual confirmation of the correct positioning and function of the tube exchange catheter it was decided that the absence of a cuff and a poorly sealed left main bronchus were most likely contributory factors [6]. Later, it was shown that a haemothorax, due to blood loss into the dependant pleura throughout the surgery, had caused this life‐threatening event and 1500 ml of blood was drained during the recovery period.…”
Section: Case Reportmentioning
confidence: 99%
“…A sterile uncut, 7.5 mm cuffed tracheal tube was passed over the tube exchange catheter into the left main bronchus and the position of the tube and cuff confirmed using the fibreoptic bronchoscope and under direct vision through the operative field. Anaesthetic management became a holding exercise – adaptive (low inflation pressure, prolonged expiration) and reactive (ventilator disconnection) until the trachea was repaired and ventilation of the second lung was re‐established [5–7]. After the tracheal tube was withdrawn into the trachea and both lungs were ventilated, the patient remained stable until the end of the procedure.…”
Section: Case Reportmentioning
confidence: 99%